Práticas e relações socioespaciais e culturais nos espaços públicos de Currais Novos/RN, durante a Festa de Sant'Ana: pesquisa qualitativa e etnográfica - Medeiros, Alenuska Lucena (2019)
Space is produced by social, political and economic relations. In it there are the exchanges, the meetings, the festivities and the daily life that dynamizes the city. Among the dynamics found in the city are the popular festivals, present since the formation of most Brazilian cities. The culture of the city of Currais Novos, in the state of Rio Grande do Norte, is strongly influenced by the Roman Catholic Church, identified through religious rites and socio-spatial appropriations. However, the biggest religious festival in Currais Novos is the Feast of Sant'Ana, which has been absorbing new cultural manifestations with "profane" characteristics since the 20th century. In this process of festive resignification, it is perceived that socio-spatial and cultural practices interfere in the appropriations of individuals and groups. The aim of the present research was to analyze the socio-spatial and cultural relations of Currais Novos / RN, starting from the Feast of Sant'Ana, identifying how they contribute to the contemporary idea of the city and taking into account the spatial triad of Lefebvre and Soy. The research followed a qualitative and ethnographic approach, through observation techniques and semi-structured interviews. This methodology allowed us to approach the perception of socio-spatial practices of the shared and practiced discourse regarding public spaces and culture in Currais Novos / RN. It was concluded that the socio-spatial and cultural practices of Currais Novos are based on the re-significances of the appropriations and dominations of individuals and groups. However, it is the appropriation that will make possible the irreconcilable space, where the different identities and intentions of profit, ideology and "partying" combine.